Investigation of the digital technologies influence on the process transformation in cinema - Yu. V. Vorontsova; D. N. Koltsov (Вестник университета)
Within the sectoral structure of the national economy, audiovisual industries are parts of the cultural industry. Cinema is a particularly effective means of satisfying the human need for affective self-expression and establishing emotional communication between people. To increase the audiovisual product competitiveness, an analysis of the digital technologies impact on it was carried out in order to attract an additional audience. It is noted that modern technologies have paved the way for multifunctional devices: the creative process is increasingly becoming technological in nature. The use of digital technologies has led to the creation of high-quality films. Due to technological progress, the equipment becomes available to more participants in the film business. Digital technologies have become a powerful and accessible tool that allows non-professional artists/directors to enter the cinematic space. However, for the author’s cinema, digital technologies have only become a tool to improve picture quality, as well as expand the capabilities for the artist / director to bring their ideas to life on screen.